The effective universalization of rights. An unfinished assignment - Fernández Ruiz-Gálvez, María Encarnación (2016)
The vocation of universality of human rights is an inherent feature of the concept of human rights since its inception and gives them their sense and their own meaning as instruments of progress, emancipation, human liberation, but also protection, protection for the weakest person, for the voiceless, for those who can not defend their rights themselves. The vocation of universality of human rights requires a constant effort to overcome the exclusions, reappearing always under renewed forms, and advance toward the effective universalization of human rights, for which it is necessary to overcome the individualistic interpretation of the rights that links them exclusively to autonomy and leading to the exclusion of broad sectors of people of title and / or benefits of rights.